Reaching a Deadlock: Areas of Contention in Platform Regulation in Brazil - Michelotti, Andressa; Birchal Domingues, Leticia (AoIR Selected Papers of Internet Research, 2026)
Around the world, there is growing concern about platform regulation. In Brazil, the debate over whether and how platforms should be regulated often intensifies during critical moments, such as elections, mobilizations, and health crises. Gorwa (2024) argues that when a government possesses sufficient power to intervene in platform governance, it can drive significant policy changes. However, when government power is constrained, its ability to implement impactful policies and secure platform cooperation may be less effective. In this context, we ask: What are the key areas of contention in platform regulation? By examining two major regulatory proposals in Brazil—the Internet Freedom, Responsibility, and Transparency Act (Fake News Bill 2630/2020) and the platform work regulation (PLP 12/2024)—we aim to shed light on the challenges and potential pathways for more effective platform governance. Specifically, we focus on two crucial moments: (i) the transition from self-regulatory measures to platform governance models and/or co-regulation; and (ii) the moments when regulations stall and cooperation between public and private actors is at risk.